2014
DOI: 10.1063/1.4871487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Xe2+ ions on the micro-hollow cathode discharge driven by thermionic emission

Abstract: The influence of Xe 2 þ dimer ions and excited Xe* atoms on the hollow cathode discharge driven by electron thermionic emission is studied using two-dimensional Particle-in-Cell Monte Carlo Collisions modeling. A comparison with the results of two-component (electrons and Xe þ ions) plasma modeling showed that the presence of the Xe 2 þ dimer ions and excited Xe* atoms in the plasma affects the plasma parameters (density, potential, and ion fluxes toward the cathode). The influence of Xe 2 þ ions and Xe* atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…The experimental setup enabled continuous arc discharge in the hollow cathode with specified inlet mass flow rate (17) and anode and keeper current (10). In these experiments, anode voltage and gas pressure inside the cathode tube were measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup enabled continuous arc discharge in the hollow cathode with specified inlet mass flow rate (17) and anode and keeper current (10). In these experiments, anode voltage and gas pressure inside the cathode tube were measured.…”
Section: Resultsmentioning
confidence: 99%
“…In [9] and [10], it was noted that the main disadvantages of fluid models [3]- [8] were assumption about non-Maxwellian electron energy distribution function (EEDF) and simplified plasma-chemical model of discharge in xenon that did not account for processes with molecular xenon ions. The results of the simulations in [9] and [10] were compared with the results of 2-D fluid models [3]- [8]. It was shown that EEDF significantly deviates from the Maxwellian one, and the presence of the second ion specie increases plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…The PIC-MCC is based on first principles and minimizes the number of assumptions made on the calculation [38]. This method has been widely employed in the analysis of various kinds of plasma discharge such as direct-current driven microdischarges [39,40], dielectric barrier discharge [41], micro-hollow cathode discharges [35,[42][43][44] etc. The PIC-MCC method proceeds as follows: first, the distributions of some 'macro particles' that represent a large number of real charged particles determines the charge-current density in the computational domain; second, we can accumulate the particle charge or current to grids, thus electromagnetic field in the plasma can be obtained by solving Maxwell equations; then the velocities and positions of all particles are updated based on the electric field and magnet field using the leap-frog algorithm [45], during which the collisions between particles and boundary conditions are dealt with; finally, plasma parameters such as particle number densities and plasma potential can be obtained, and the overall motion of the plasma is obtained by the sum of all particle orbits.…”
Section: Pic-mcc Modelmentioning
confidence: 99%
“…Both of these also agree with the expectations of the theory. Other PIC simulations in mixtures have been conducted at conditions where two-stream instabilities are not predicted to occur in the presheath [37,38] (see [9] for an analysis of the stability conditions). In both of these cases, the ion speeds were observed to be the individual sound speed at the sheath edge, which is also consistent with the theory.…”
Section: Transport Effectsmentioning
confidence: 99%